1983
DOI: 10.1099/0022-1317-64-5-1121
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Sindbis Virus E1 Glycoprotein Induced by Monoclonal Antibody Binding

Abstract: SUMMARYA monoclonal antibody (30.2) raised against Sindbis virus is able to precipitate both E1 and PE2 from [35S]methionine-labelled infected cells solubilized with non-ionic detergent. Addition of SDS to the lysate abolishes the precipitation of PE2 without affecting that of El, thus demonstrating that the antibody is specific for El. Other Sindbis El-specific monoclonal antibodies (30.11 and 30.12) precipitate only El, even from lysates containing only non-ionic detergent, and their presence in such a lysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…4C). Similar epitope-specific antibody-mediated structural changes have also been described for other viruses (62)(63)(64). In the case of HIV, they were implicated in the enhanced antigenicity of neutralizing antigenic sites involving the V3 loop of gp 120 after immunization with ICs containing the HIV gp 120 (28,65).…”
Section: Discussionsupporting
confidence: 60%
“…4C). Similar epitope-specific antibody-mediated structural changes have also been described for other viruses (62)(63)(64). In the case of HIV, they were implicated in the enhanced antigenicity of neutralizing antigenic sites involving the V3 loop of gp 120 after immunization with ICs containing the HIV gp 120 (28,65).…”
Section: Discussionsupporting
confidence: 60%
“…To date only the epitopes on the viral surface glycoproteins have been well characterized using monoclonal antibodies (MAbs) (Chanas et al, 1982;Clegg et al, 1983;Davis et al, 1987;Roehrig et al, 1980Roehrig et al, , 1982Stanley et al, 1985;Yamamoto et al, 1985). In order to identify conserved group-reactive antigenic determinants on the NC protein of alphaviruses, MAbs were raised against SF virus.…”
Section: Discussionmentioning
confidence: 99%
“…In three viruses of the WN subgroup, this synergism was also observed using mixtures of anti-JE MAbs from different MAb groups. Some investigators have reported that the binding of antibodies to certain epitopes on virus protein induces conformational changes in distant parts of the molecule and results in the increased avidity of other antibodies (Clegg et al, 1983;Heinz et al, 1984a;Lubeck & Gerhard, 1982). Such conformational changes or steric hindrance of important N sites for virus infection may cause the synergistic N of other flaviviruses.…”
Section: Discussionmentioning
confidence: 99%